O trabalho com o gênero carta de solicitação a partir de sequências didáticas : potencialidades de uma abordagem - Nordi, Cristiane (Universidade Federal de São Carlos, 2013)
This research aims to discuss the work with gender request letter in school, from a proposal for intervention, along with a group of sixth grade of elementary school to a public school in São Paulo. The theoretical framework is based on studies of Social Interactionism (Bakhtin, 2000, 2002, Vygotsky, 1989) and specifically in studies arising from Sócio-Discursive Interacionism, didactic in his shed on the use of textual genres in the classroom (Bronckart; Dolz, NOVERRAZ and SCHNEWULY, 2004, 2005, 2006, 2007). In order to develop a work that integrates the language practices, which favor the use of language and situated to contribute to the effective development of the students, it was decided methodologically by developing a didactic sequence (SD), as a tool for teaching and data collection for research. Thus, we adopt the perspective of Action Research, finding the qualitative paradigm a viable way for the development of this research-oriented problem solving and / or processing of a given situation. The results achieved with the research showed some potential of SD methodology while working with the language. On the one hand, its use promoted the development of contextualized writing students, and collaborate with the experience of a language teaching situated on the real needs of the learners. Also made to reflect the importance of starting the learning of the grouping of genres argued early so that children can develop all the skills regarding this complex speech genre, and thus ensure a consistent learning that seeks inclusion of students in practices of communicative activities. The approach from Didact Sequence proved to be, in our research, a useful means to identify the strengths and difficulties of students and to better align the work of the teacher in the classroom. Thus, the results demonstrated that the development of Didact Sequence was productive and viable in our research context, made possible because the teacher work formal content (spelling, verbal inflection) and textual production while, in addition, the most important, that was to make students understand the social function of gender letter of request. Finally, but not least, the elaboration of didactic model and the very fact that the SD characterized as action research enabled us apropriássemos of theories relevant to teacher education, which led us to the conclusion that the only change understand and practice when we appropriate theories appropriate to the social nature of language.
Keywords: Linguística; Interacionismo sócio-discursivo; Gêneros textuais; Seqüência didática; Sócio-Discursive Interacionism; Textual genres; Didact sequence; LINGUISTICA, LETRAS E ARTES::LINGUISTICA